Operationalizing sustainable transparency in software ecosystems portals - Moura, Marcus Ferreira de; Zacarias, Rodrigo; Santos, Rodrigo; Lago, Patricia (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi_estendido.2025.246859, 2025)
Transparency is a key element in software ecosystems (SECO) and promotes trust, collaboration, and accountability. However, current transparency measures focus mainly on technical aspects, such as code openness or Application Programming Interface (API) accessibility, while focusing less on social, organizational, and economic characteristics. This paper introduces a Key Performance Indicator (KPI) framework to operationalize sustainable transparency in SECO portals. Our mixed method begins with a longitudinal review of previous research and proceeds to define KPI aligned with measurable goals. Expert evaluations will be conducted, through structured interviews, to assess the feasibility of the proposed KPI. In addition, a feasibility study in a representative SECO setting will explore how this framework can strengthen existing transparency efforts and inform continuous improvements in ecosystem management. The goal of this research is to contribute to the field of information systems by providing actionable data-driven insights that can enable SECO management teams to monitor and improve transparency across multiple characteristics and thus support the long-term sustainability of digital platforms.